Implementation Strategy of Multi-Domain Operations Post Law No. 21/2025 on Airspace Management: Legal-Defense Perspectives - Edward Elisa Pattiwael; I Gde Prabawa Wicaksana; Budi Santoso; Tri Budianto; Munip Suharmono; Isa Hidayat (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The defense capability of a nation in conducting Multi-Domain Operations (MDO) has become an essential requirement in facing modern multidimensional warfare threats. In Indonesia, the enactment of Law No. 21 of 2025 concerning Airspace Management provides a more dynamic legal foundation for integrating airspace management into the national defense system. However, the implementation of this law still faces various gaps, including regulatory disharmony between civilian and military perspectives, institutional fragmentation, data silos between systems, and dependence on foreign technology. This study employs a qualitative descriptive-analytical approach based on data from the Seskoau A-64 workshop to analyze the real conditions of MDO implementation readiness following the enactment of Law No. 21/2025. The analysis reveals five main strategic issues hindering cross-domain interoperability. To address these, an implementation strategy is formulated using the McKinsey 7S framework, covering shared values, structure, systems, style, staff, skills, and strategy. This strategy is then operationalized into a phased roadmap (short-term, medium-term, and long-term) along with a stakeholder role matrix. The study concludes that policy harmonization, strengthening of cross-sectoral institutions, integration of network-centric command and control systems, and achievement of technological self-reliance are the primary prerequisites for successful MDO implementation in Indonesia. Without an applicable and measurable roadmap, the potential of Law No. 21/2025 as an enabler for national air defense will not be optimally realized.